2009
DOI: 10.1002/gcc.20692
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the molecular signature of the interstitial deletion 7q subgroup of uterine leiomyomata using a paired analysis

Abstract: Uterine leiomyomata (UL), the most common neoplasm in reproductive-age women, have recurrent cytogenetic abnormalities including del(7)(q22q32). To develop a molecular signature, matched del(7q) and non-del(7q) tumors identified by FISH or karyotyping from 11 women were profiled with expression arrays. Our analysis using paired t-tests demonstrates this matched design is critical to eliminate confounding effects of genotype and environment that underlie patient variation. A gene list ordered by genome-wide sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…In addition to F3 and IL8 through data mining, we identified a significant number of other genes as possible direct and indirect targets of miR-106bϳ25 in TF324 cells, also expressed in leiomyomas with and without del7q22 (16). These results further illustrated the potential consequence of chromosomal rearrangements, such as del7q22, not only on the expression of many genes located at these regions but also their downstream target genes with functional association with cell cycle progression, apoptosis, inflammation, angiogenesis, and tissue turnover, influencing the outcome of leiomyoma pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to F3 and IL8 through data mining, we identified a significant number of other genes as possible direct and indirect targets of miR-106bϳ25 in TF324 cells, also expressed in leiomyomas with and without del7q22 (16). These results further illustrated the potential consequence of chromosomal rearrangements, such as del7q22, not only on the expression of many genes located at these regions but also their downstream target genes with functional association with cell cycle progression, apoptosis, inflammation, angiogenesis, and tissue turnover, influencing the outcome of leiomyoma pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Based on 1.5-fold change cutoff, the expression of 992 genes, including F3 and IL8, were either directly and/or indirectly altered by miR-106bϳ25 trsnsduction of which the expression of 661 gene was down-regulated and 331 genes were up-regulated as compared with untreated control (Supplemental Table 1). Through data mining we assessed whether the expression of these 992 genes are altered in del(7q) and non-del(7q) leiomyomas using the data sets reported by Hodge et al (16). The analysis identified 226 of the 992 genes as differentially expressed (P Ͻ 0.05 cutoff) in matched del(7q) and nondel(7q) leiomyomas and in TF324 cells transuding miR-106bϳ25 cluster ( Fig.…”
Section: Identification Of F3 and Il-8 As Targets Of Mir-93/106bmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the myometrial cell population that gives rise to these tumors has not been identified [6,7]. Several recurrent genetic aberrations, such as chromosome 12 trisomy, deletions in 7q, and mutations in genes encoding mediator complex subunit 12 (MED12) or high mobility group AT-hook 2 (HMGA2) have been reported in leiomyomas [8][9][10][11]. As in other diseases, these genetic abnormalities occurring in tumor stem cells are thought to play pivotal roles in the tumorigenesis of leiomyomas.…”
Section: Introductionmentioning
confidence: 98%